2015
DOI: 10.1038/onc.2014.448
|View full text |Cite
|
Sign up to set email alerts
|

EGFRvIII-mediated transactivation of receptor tyrosine kinases in glioma: mechanism and therapeutic implications

Abstract: A truncation mutant of the epidermal growth factor receptor, EGFRvIII, is commonly expressed in glioma, an incurable brain cancer. EGFRvIII is tumorigenic, in part, through its transactivation of other receptor tyrosine kinases (RTKs). Preventing the effects of this transactivation could form part of an effective therapy for glioma; however, the mechanism by which the transactivation occurs is unknown. Focusing on the RTK MET, we show that MET transactivation in U87MG human glioma cells in vitro is proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 35 publications
1
38
0
1
Order By: Relevance
“…For example, EGFRvIII transactivation of the hepatocyte growth factor (HGF) receptor (MET) leads to resistance to rilotumumab, an antibody therapy that blocks tumor growth by neutralizing HGF and inhibiting HGF-mediated MET signaling (Pillay et al 2009). Similarly, EGFRvIII receptors can increase the activation of other RTKs through their inappropriate retention at the cell surface (Greenall et al 2015) or by forming heterodimers that cause aberrant RTK activation and increased mitogenic signaling (Greenall et al 2015).…”
mentioning
confidence: 99%
“…For example, EGFRvIII transactivation of the hepatocyte growth factor (HGF) receptor (MET) leads to resistance to rilotumumab, an antibody therapy that blocks tumor growth by neutralizing HGF and inhibiting HGF-mediated MET signaling (Pillay et al 2009). Similarly, EGFRvIII receptors can increase the activation of other RTKs through their inappropriate retention at the cell surface (Greenall et al 2015) or by forming heterodimers that cause aberrant RTK activation and increased mitogenic signaling (Greenall et al 2015).…”
mentioning
confidence: 99%
“…It is noteworthy that EGFRvIII is tumorigenic, in part, through its transactivation of other RTKs, including AXL, PDGFR, vascular endothelial growth factor receptor 3 and fibroblast growth factor receptor [24][25][26] . Further, many new studies are focusing on elucidating the cross-talk among EGFRvIII and the hepatocyte growth factor (HGF) receptor (MET), aimed to provide innovative strategies for treating EGFRvIII-expressing gliomas [25,26,33,34] .…”
mentioning
confidence: 99%
“…In contrast, the second-generation inhibitors, such as lapatinib, even if results more potent at binding and inhibiting EGFRvIII, has demonstrated intratumoral levels that result inadequate to induce inhibition of GBM tumor growth [22] . Apart from these pharmacological factors that dictate the low response of EGFRvIII to small molecule TKIs, multiple mechanisms of resistance to EGFR inhibition have been described and include: i) the loss of phosphatase and tensin homolog, which keeps the active signaling through the phosphatidylinositol 3 kinase pathway [23] , ii) the co-activation of multiple receptor tyrosine kinases (RTKs) in the same tumor [24][25][26] and iii) the dependence on other non-amplified, non-mutated RTKs by a receptor "switching" mechanism [27] . The first clinical and biologic evidence for this last mechanism has been provided by Akhavan D et al [27] , that reported the existence of a transcriptional repressive mechanism by which EGFRvIII represses platelet-derived growth factor receptor β (PDGFRβ) expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…29 Unlike EGFR, EGFRvIII has not been detected in normal tissues, but has been identified in tumors. [30][31][32] In recent years, aptamers have been developed as a novel recognition probes constituted with uniquely folded short RNA or ssDNA oligonucleotides which can bind to the targets with high specificity and affinity. 33 In addition, compared with antibodies or polypeptides, aptamers have many advantages including lower immunogenicity, thermal stability, ease of modification, higher specificity, smaller size, lower production cost, and no toxicity.…”
mentioning
confidence: 99%